Asuhan Keperawatan Keluarga Pada Tn. W Dengan Gangguan Sistem Persyarafan: Stroke Di Desa Tonjong Dukuh Karangjati Kecamatan Tonjong Kabupaten Brebes - Putri Selvi Febriyana; Siti Fatimah (STIKES Columbia Asia Medan, 2026)
Background: Community nursing is a service process that is a combination of nursing and public health. Family nursing care is health services focused on the family where the entire process from assessment, diagnosis, planning, implementation to evaluation involves all family members both in healthy and sick conditions. The elderly are individuals in the age range of 60 years and above. Stroke is a disorder of brain function that appears suddenly accompanied by clinical signs both local and global in nature that last more than 24 hours caused by disruption of blood flow to the brain. Objective: To provide family nursing care to Tn. W with Neurological System Disorders: Stroke in Karangjati Village RT 02 RW 05 Tonjong District, Brebes Regency. Methods: This scientific paper is compiled using a descriptive narrative study approach following the stages of the nursing process including assessment, diagnosis, intervention, implementation, and evaluation. Data collection techniques include interviews, observation, physical examination, and documentation studies. Results: Nursing diagnoses that emerged were physical mobility impairment and knowledge deficit. Nursing interventions for physical mobility impairment included recognizing health problems and understanding stroke management, particularly related to mobilization through passive and active range of motion (ROM) exercises. For knowledge deficit, interventions included health education about stroke using educational media. Conclusion: After implementation over three days (December 27–29, 2025), the physical mobility impairment problem was partially resolved and knowledge deficit was resolved. It is expected that patients can increase their knowledge about health, particularly stroke disease.